Economic interdependence and security. - Lee, Keng Min. (2008)
This paper seeks to discuss the nature of economic cooperation within the Asia Pacific Economic Cooperation (APEC) and East Asia Economic Caucus (EAEC) and the extent of economic interdependence in the region and its implications for security.